COVID-19 vaccine hesitancy among the university students and personnel - Jomell Miranda Santiago; Angelo R. Santos; Analyn M. Gamit (International Journal of Public Health Science (IJPHS), 2023)
A delay in accepting or refusing a vaccination despite the availability of vaccination services is described as vaccine hesitancy. The vaccine hesitancy among the Filipinos is a significant challenge to achieving herd immunity. Thus, this study was conducted to determine the COVID-19 vaccine hesitancy of Nueva Ecija University of Science and Technology students and staff. Total sampling and descriptive study methodology were employed. To gather information about the profile, information sources, and hesitation regarding the COVID-19 vaccine, a questionnaire was created. Both informed consent and permission to conduct were secured. Researchers used a variety of statistical tools to assess the data. The respondents’ likely reasons to get vaccinated were to protect themselves and others, and the recommendation from a healthcare provider can help encourage those hesitant to get vaccinated. Moreover, the main reasons for their hesitancy were their fear of the side effects, and poor knowledge about the vaccine. With this, educational programs meant to educate those individuals who had vaccine hesitancy must be conducted. Moreover, vaccine hesitancy must be monitored, as it is expected to vary over time. Therefore, campaigns to disseminate the importance of the vaccine in the nation's public health must be continuously conducted for all types of diseases.